Naphthalene Derivates from Bawang Tiwai Bulb Eleutherine Bulbosa in Borneo - Salam, Supriatno; Hikmawan, Baso Didik; Samsul, Erwin; Herman, Herman; Ahmad, Islamudin; Rijai, Laode; Nafiah, Mohd Azlan (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
Naphthalene derivative compounds named Eleutherol (1) and Eleutherol C (2) have been isolated from Bawang Tiwai Bulb Eleutherine bulbosa. We tested its cytotoxic activity against T47D breast cancer cells in vitro after isolating compounds 1 and 2 from the EtOH extract using conventional chromatography methods. Their chemical structures were elucidated based on spectroscopic analysis, including IR, HR-TOFMS, 1D, and 2D NMR, and by comparison to those related spectra previously reported. Compounds 1 and 2 were tested for their cytotoxic effects against T47D breast cancer cells and showed moderate cytotoxicity against T47D breast cancer cells with IC50 values of 117.15 and 80.21 µM, respectively, compared with cisplatin 24.07 µM.